Preventing infection and maintaining immune function using nutritional strategies - Naulleau, C. (Sircuit, 2016)
The high intensity training of elite sport significantly increases the risk of illness and reduces the effectiveness of the immune system to fight infection is reduced. Nutritional strategies in relation to sleep, stress, recovery, and supplements, implemented before, during and after workouts and travel can help to prevent infections in athletes and maintain a strong and healthy immune system. Recommendations include - Isolating athletes who are ill, working with a nutritionist to address the specific needs of the athlete, reducing outside stressors and getting adequate sleep.